2010
DOI: 10.1108/17538371011056084
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in contract terms and contracting processes

Abstract: PurposeNew business models, such as life‐cycle contracting, challenge the narrow and static understanding of contracts with hard and precise terms. The aim of this paper is to examine how flexibility could be incorporated into contracting processes.Design/methodology/approachThe data of the paper have been gathered applying the triangular method; first, by interviewing key personnel participating in contracting at eight Finnish firms; second, examining contract and other documents of those companies; and third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 24 publications
1
54
0
Order By: Relevance
“…This is in line with Nystén-Haarala et al 's (2010) findings that introducing flexibility into contracts via relational methods relies on good personal relationships between the actors. As mentioned in the introduction, Hertogh and Westerveld (2010) stress that interaction is an important instrument to manage the needs of stakeholders, and to anticipate the consequences of potential changes.…”
Section: Disclosure Statementsupporting
confidence: 76%
See 1 more Smart Citation
“…This is in line with Nystén-Haarala et al 's (2010) findings that introducing flexibility into contracts via relational methods relies on good personal relationships between the actors. As mentioned in the introduction, Hertogh and Westerveld (2010) stress that interaction is an important instrument to manage the needs of stakeholders, and to anticipate the consequences of potential changes.…”
Section: Disclosure Statementsupporting
confidence: 76%
“…Based on a study on flexibility in health care PPP projects, Cruz and Marques (2013) propose in line with this notion a double entry matrix based on real options theory as a new model for contract flexibility. According to Nystén-Haarala et al (2010), flexibility is often introduced in contracts through social methods, relying on good personal relationships between business partners rather than through the contract itself. Therefore, contract documents often do not contain mechanisms for dealing with contingencies.…”
Section: Contract Flexibilitymentioning
confidence: 99%
“…Other precautions for risk are performance requirements (Nystén-Haarala et al, 2010). Both the STA and the contractors have indicated that the evaluation, both during the contract and afterwards, will be difficult.…”
Section: Performance Requirements and Evaluationmentioning
confidence: 99%
“…Implementing the IPSO as a business model is not without its challenges; as for any change in the business model, the risks change as well (Nystén-Haarala et al, 2010). An IPSO implies taking over some of the customer's processes, which is a major risk for the provider (Meier et al, 2010).…”
Section: Long-term Contracts and Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation